Gender Differences in Basic Physics Laboratory Skills among Biology Education Students: A Quantitative Analysis - Taufik, Muhammad; A, Syahrial (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2023)
This study investigated gender differences in physics laboratory skills among biology education students. A total of 90 students were recruited from three biology education classes at a university in Indonesia. The students completed five physics laboratory activities, and their performance was assessed using a rubric that measured skills in using laboratory equipment, data analysis, and communication. The results showed that there were no significant differences in physics laboratory skills between male and female students. However, there were some trends that suggest that female students may have a slight advantage in data analysis skills. These findings suggest that gender differences in physics laboratory skills may be minimal, and that both male and female students are capable of achieving high levels of performance in physics laboratory courses.